Ontological Foundation for Representing Metaphors as part of LOD - Panayiotou, Christiana (My University, 2024)
The main goal of this study was to lay the foundation for the representation of written metaphors as Linked Open Data (LOD) on the Semantic Web (SW). To achieve this goal, this study proposed concepts and properties that allow metaphors from different domains to be linked. The use of the proposed formalism was illustrated through a case study of biblical data extracted from text, represented, populated, and queried to demonstrate the usage of the proposed ontological concepts. The proposed model reuses the FaBio bibliographic ontology to represent the bibliographic information of metaphoric data, and the OWL-Time ontology to represent the temporal aspects of events associated with metaphors. Examples from different domains are used to illustrate the implementation and population of concepts related to time instants and intervals. The notions of approximation and uncertainty in the description of the time of occurrence of events associated with the creation, publication, and translation of metaphors were also discussed. An important aspect of the proposed formalism is the representation of the qualities attributed to the vehicle and the target concepts of conceptual metaphors. This enables the identification of symbolism and interpretation of concepts in different contexts and domains. The proposed formalism was tested against a number of queries and proved to satisfy the information requirements.
Keywords: knowledge representation; linked data; natural language processing; ontologies; Semantic web